180 Systematic Review and Meta-Analysis of Exercise Therapy for Venous Leg Ulcer Healing and Recurrence. (28th February 2022) - Turner, B.R.H.; Jasionowska, S.; Machin, M.; Onida, S.; Webster, C.; Davies, A.H.
Abstract: Aim: National guidelines recommend regular exercise for individuals with venous leg ulceration, yet data for the effect of exercise on ulcer healing and recurrence are sparse. This study aimed to quantify the evidence for exercise in venous ulcer healing with the primary outcomes of proportion of healed ulcers and rate of ulcer recurrence. Secondary outcomes were compliance and adverse events. Method: The review followed PRISMA guidelines using a registered protocol (CRD42021220925). Medline, Embase and Cochrane Databases were searched on 15 th March 2021 and included articles comparing exercise to compression therapy. Meta-analysis was performed to pool the data. Results: After screening 994 articles, six reports were included with 109 participants allocated to exercise and 113 to compression. All articles were randomised-controlled trials and reported ulcer healing at 12 weeks, with a pooled relative risk of 1.35 ulcers for exercise versus compression (95% CI 1.07 – 1.71). Only one article reported on recurrence and data pooling was not performed, but no difference between exercise and usual care was demonstrated. Adverse events were inadequately reported and seen to be more frequent in the exercise arm. Compliance with exercise ranged from 33–81%. Conclusions: There is increasing evidence for exercise as an adjunct to ulcer healing, however, trials were low quality with high risk of bias. This is a crucial innovation as many ulcers recur or fail to heal in spite of surgical correction of underlying venous insufficiency. There is paucity of evidence examining leg ulcer recurrence after exercise programmes and currently no evidence of benefit.